Estudo do Catalisador (10%Ni-1%Cu) suportado na oxidação parcial indireta do Etanol - Furtado, Andréia Cristina (2004)
In the present work, the reaction of indirect partial oxidation of the ethanol for production of H2 for fuel cells was studied in catalysts 10%Ni-1%Cu (% mass) on different supports (Al2O3, SiO2-50, SiO2-200, Nb2O5 and CeZrO2). The catalysts were prepared by coimpregnation, leaving from aqueous solution of the respective nitrates, dry and calcined. The oxide phases of those catalysts were characterized by UV-vis DRS, DRX, RTP and superficial area BET, while analyses of DRX of the reduced-passivaded catalysts and TPD-H2 were used to identify the phases and, mainly, to calculate the dispersion of the present metallic phases. After being reduced to 600oC (3h) under flow of pure H2, the catalytic tests were realized to 400oC using 10 mg of catalyst and 50 mL/min of a reactional mixture containing air, ethanol and water - EtOH/O2 = H2O/EtOH = 2. The results revealed the presence of the phase NiO in all of the calcined samples and a strong interaction of this with the support, forming oxide species of difficult reduction, including the probable formation of NiAl2O4 and of nonstoichiometric NiNb2O6. The profiles of TPD-H2 presented two dessorption areas, the first associated to the hydrogen quimissorved in Ni and the second attributed to stored H2 and dessorved from the support by spillover, more significant in reductable supports and of high superficial area. The conversions of obtained ethanol were superior to 70%. The catalysts supported in CeZrO2 and Al2O3 showed larger selectivity to H2, CO and CO2, in spite of the first has shown the least active for the conversion of the ethanol. The acetaldehyde and eteno presences indicate that the partial oxidation of ethanol to the first product constitute the initial step for H2 and CO2 production in the studied conditions.